What a girl wants - Buzzell, Matthew; Massie, Elizabeth; Briccs, Jacob; Media Education Foundation; CHC Productions; The Teresa and H. John Heinz III Foundation ([Northampton, Mass.] : CHC Productions : Media Education Foundation [distributors], 2000)
Eleven girls ages 8 to 16 and two classrooms of middle and high school students discuss their views on mass media and how it impacts their lives
Title from title screen
Director of photography, Matthew Buzzell; music, Sean Eden; editor, Jacob Bricca sound editor, Randy Perry
Keywords: Girls -- Psychology; Mass media and teenagers; Women in mass media; Teenage girls -- Psychology